Pomiar jakości usług publicznych jako niezbędny element controllingu w gminie - Borowiec, Leszek (Measurement of public services quality as an essential element of controllership in a local government, 2006)
The issues connected with measurement of quality of public services offered by a local government as an essential element of controllership have been presented in the article. A local government is responsible for rendering administrative, social and technical services to its inhabitants. Without any measurements one cannot talk about making use of control function in a controllership system, which consequently blocks managing the process of services rendering. In order to measure and evaluate quality of public services in terms of its productivity, effectiveness and availability, it is necessary to define indicators properly, establish methods of measurement and rules of concluding and interpreting the results. In the second part of the paper selected indicators used in the process of technical services evaluation have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 43-52